2023
DOI: 10.1007/s10549-023-06882-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome in metastatic lobular breast cancer in the prospective German research platform OPAL

Abstract: Purpose Evidence about routine treatment and outcome of patients with invasive lobular cancer (ILC) is limited, especially regarding metastatic disease. Here we present prospective real-world data of patients with metastatic ILC (mILC) as compared to patients with metastatic invasive ductal cancer (mIDC) receiving systemic therapy in routine care in Germany. Methods Prospective data on patient and tumor characteristics, treatments, and outcomes of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…
I read with great interest the article by de Thill et al [1] in which they presented prospective real-world data of patients with metastatic invasive lobular cancer (mILC) as compared to patients with metastatic invasive ductal cancer (mIDC) receiving systemic therapy in routine care in Germany. They concluded that ILC histopathology was not associated with a better clinical outcome in multivariate analysis, suggesting the need for more tailored treatment strategies for patients with the lobular subtype, despite patients with mILC presenting with some favorable prognostic factors.
…”
mentioning
confidence: 99%
“…
I read with great interest the article by de Thill et al [1] in which they presented prospective real-world data of patients with metastatic invasive lobular cancer (mILC) as compared to patients with metastatic invasive ductal cancer (mIDC) receiving systemic therapy in routine care in Germany. They concluded that ILC histopathology was not associated with a better clinical outcome in multivariate analysis, suggesting the need for more tailored treatment strategies for patients with the lobular subtype, despite patients with mILC presenting with some favorable prognostic factors.
…”
mentioning
confidence: 99%